Limitation of resources and invisibility in the media against women campaigning as a form of political violence based on gender - Castrejón Mata, Carmen (2023)
During the 2017-2018 electoral process in Celaya, Guanajuato, Mexico, manifestations of political violence against participating women were evidenced through verbal attacks, the dissemination of images, and denigrating words on social networks and the media, which shows that gender stereotypes regarding women's political participation continue to be reinforced. The aim was to identify these gender stereotypes regarding their participation in political life from the political sphere themselves, the media and civil society. This work uses a qualitative approach with a grounded theory research design, in this study the following techniques were used: semi-structured interview, in-depth interview, field diary, review and document analysis. The sample consisted of women who participated in some popularly elected office during the 2017-2018 electoral process as municipal president, regiduría and local deputation. It was found that the normalization of violence also occurs in political spaces, and this may even complicate the processes for recognizing violence and denouncing it, since, once women victims of some type of violence are usually re-victimized and stigmatized by the institutions themselves and often by society. Violence against women transcends different spaces: domestic, community, work, institutional and political.